1986
DOI: 10.1152/jn.1986.56.4.1196
|View full text |Cite
|
Sign up to set email alerts
|

The sensory contribution of a single vibrissa's cortical barrel

Abstract: The sensory contribution of the cortex containing the cortical barrel of the C1 vibrissa was studied in rats using the ablation-behavior method. Three independent experiments were performed, each requiring stimulus transduction by the C1 vibrissa but varying in their perceptual demands. The first required detection of sinusoidal oscillations of the vibrissa generated by an oscillating airstream directed vertically onto the vibrissa tip. The second required detection of a change in rate of the oscillation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
234
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(252 citation statements)
references
References 0 publications
17
234
1
Order By: Relevance
“…It has been shown that rats are capable of amazingly fine discriminations of surfaces (GuicRobles et al, 1989;Carvell and Simons, 1990) and apertures (Krupa et al, 2001), and that discrimination of textures and object forms are optimized by active scanning movements (Carvell and Simons, 1995;Harvey et al, 2001;Prigg et al, 2002). Finally, the detectability of 1-3°whisker deflections applied by a sinusoidally modulated air stream (at 0.1-32 Hz) in mobile rats was demonstrated in the only study so far that attempted to use parameterized whisker deflections (Hutson and Masterton, 1986). However, none of these studies achieved the precision of stimulus control that is needed to causally relate physical properties of the stimulus to neuronal activity and to the percept.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that rats are capable of amazingly fine discriminations of surfaces (GuicRobles et al, 1989;Carvell and Simons, 1990) and apertures (Krupa et al, 2001), and that discrimination of textures and object forms are optimized by active scanning movements (Carvell and Simons, 1995;Harvey et al, 2001;Prigg et al, 2002). Finally, the detectability of 1-3°whisker deflections applied by a sinusoidally modulated air stream (at 0.1-32 Hz) in mobile rats was demonstrated in the only study so far that attempted to use parameterized whisker deflections (Hutson and Masterton, 1986). However, none of these studies achieved the precision of stimulus control that is needed to causally relate physical properties of the stimulus to neuronal activity and to the percept.…”
Section: Discussionmentioning
confidence: 99%
“…Psychophysical studies conducted so far mostly used nonrestrained, freely moving rats sampling stimuli by using their own body and whisker movements Simons, 1990, 1995;Harvey et al, 2001;Krupa et al, 2001). Hutson and Masterton (1986) are the only investigators so far who attempted to quantify psychophysical detection thresholds with varying kinematic deflection parameters; however, rats in that study were free to move their head, and control of whisker deflection generated by air streams did not reach the level of stimulus control deemed necessary: micrometer precision at a millisecond time scale. The relative coarseness of stimulus application that is characteristic for previous behavioral studies stands in stark contrast to the high spatiotemporal precision of stimuli used for electrophysiological investigations in anesthetized animals.…”
Section: Introductionmentioning
confidence: 99%
“…Hutson and Masterton (1986) reported the puzzling finding that lesions of the barrel field in primary somatosensory cortex had virtually no effect on the rats' abilities to perform a whisker-mediated vibrotactile discrimination task. This finding poses a problem for every study investigating the contribution of barrel cortex to whiskermediated detection and discrimination abilities.…”
Section: Discussionmentioning
confidence: 99%
“…S1 is necessary for tactile somatosensory perception in rodents [7][8][9][10][11][12][13] . The role of S1 in thermal perception, however, is under debate, 3 with three studies concluding that rodent S1 is not involved [14][15][16] and another concluding that it is 17 .…”
Section: Introductionmentioning
confidence: 99%